Examining the effectiveness of advertising on the intentions of Hong Kong by mainlanders: the moderating role of ideal self-congruity - Gong, Shuhui; de Costa, Feroz; Mohd Hasan, Nurul Ain; Liu, Lu (Malque Publishing, 2026)
Hong Kong is gradually losing its tourism appeal to mainland visitors. This study investigates the efficacy of advertising strategies in rekindling mainland Chinese tourists' interest in revisiting Hong Kong. Grounded in Reader-Response Theory (R-RT), the Theory of Reasoned Action (TRA), and Self-Congruity Theory (SCT), this research examines the psychological mechanisms influencing Generation Y revisit intentions. A cross-sectional survey collected data from 404 respondents, analyzed using Structural Equation Modeling (SEM) via Smart PLS 4. The findings reveal that both cultural and emotional effectiveness in advertisements positively shape destination image, with emotional effectiveness exerting a stronger influence. Emotional connections fostered through advertisements enhance tourists’ evaluations of Hong Kong as a destination, thereby strengthening their revisit intentions. Furthermore, the alignment between the content of advertisements and tourists' ideal self-images significantly amplifies these effects. This congruence suggests that ads appealing to an aspirational self-concept create deeper connections, motivating return visits. The results highlight the importance of emotionally resonant and culturally enriched advertisements in enhancing destination appeal. For Hong Kong to maintain its competitiveness in the tourism market, advertisers should prioritize storytelling that evokes emotions and showcases cultural uniqueness while aligning with the idealized identities of Generation Y travelers. This research contributes to the theoretical understanding of advertising effectiveness by integrating R-RT, TRA, and SCT into the tourism context. Practically, it offers actionable insights for creating impactful advertising strategies aimed at increasing revisit intentions. By leveraging emotionally charged and culturally rich messaging, Hong Kong can better connect with mainland Chinese tourists and restore its position as a favored destination.